Leveraging MANETs for Healthcare Improvement in Rural Botswana - Mabina, Alton; Seropola, Boago; Rafifing, Neo; Kalu, Kalu (Journal of Information System and Informatics, 2024)
Rural health facilities in Botswana face significant challenges, including limited infrastructure, poor communication networks, and inadequate access to medical resources, which hinder quality healthcare delivery. This study investigates the feasibility and benefits of implementing Mobile Ad hoc Networks (MANETs) in these underserved areas. A MANET is a decentralized wireless network where devices communicate directly with each other without relying on fixed infrastructure, allowing dynamic, self-configuring connections. Key solutions proposed include integrating MANETs with solar-powered systems to ensure continuous operation, developing localized health information systems to enhance data accessibility, and implementing community training programs to build local technical capacity. Additionally, designing resilient network architectures and collaborating with local telecom providers for hybrid solutions can improve reliability and coverage. Utilizing MANETs for real-time health monitoring and emergency alerts can enhance patient outcomes and response capabilities. The real-world implementation of MANETs is expected to improve emergency response times, reduce healthcare delivery delays, and facilitate faster decision-making in critical situations. This paper highlights the potential of MANETs to address healthcare disparities between rural and urban areas by providing sustainable, scalable, and reliable communication infrastructure. Future research should focus on extensive pilot programs, empirical data collection, and exploring the integration of advanced technologies to further enhance healthcare delivery in rural Botswana. These findings aim to inform policymakers and healthcare providers on adopting MANET technology to improve rural healthcare systems.